The Emerging Roles of Human Resource Managers: The Post-Covid-19 Experience in Nigeria - Abel Segun Adesanya; Christopher Femi Ogunlusi; Babalola Oluwayemi Olginni; Abiola Jamiu Eniayewu; E. A. Olowu (Papanda Publishier, 2023)
The study focused on the emerging roles of human resource managers with a focus on post-COVID-19 using the Nigerian experience as the unit of analysis. It was identified among others that the advent of Coronavirus caused the world at large to suffer many consequences mainly in human health and the workplace was not excluded. The secondary source of data collection was used to elicit information and exploratory research design was adopted for the study. It was found that the world of work in Nigeria was locked down as a preventive measure to curb the spread of the virus leading to the emergence of a new order in the workplace where work can be done from home, remote area and virtual meeting takes precedence over face-to-face interaction. It was concluded that the focus of Human Resource (HR) managers’ role should be on the well-being, health, safety, and security of employees, technology, and communication as well as reconfiguration of workflow. Thus, recommended that HR managers should avoid or be against developing a one-size - fit - all strategy to remain relevant or survive the pandemic.